I have a math answer example which shows this, (and underlined numbers and/or variables means over or devided by)
step 1 = sqrt(x+h)-sqrt(x)
h
2 = sqrt(x+h)-sqrt(x) * sqrt(x+h)+sqrt(x)
h * sqrt(x+h)+sqrt(x)
3 = (sqrt(x+h)-sqrt(x)(sqrt(x+h)+sqrt(x))
h(sqrt(x+h)+sqrt(x))
4 = ((sqrt(x+h))^2-(sqrt(x))^2)
h(sqrt(x+h)+sqrt(x))
5 = (x+h-x)
h(sqrt(x+h)+sqrt(x))
6 = h
h(sqrt(x+h)+sqrt(x))
7 = 1
sqrt(x+h)+sqrt(x)
8 = lim h ->0 1
sqrt(x+h)+sqrt(x)
9 = 1
2sqrt(x)
and I'm wondering how they decide to take the whole numerator in step 1 and multiply it to the denominator and then also in step 2 why do they switch the -sqrt(x) to +sqrt(x)? Also in step 4 to 5 to 6 it arrives at h but how, they don't really show the steps they took, if I were to do it I guess would come up with this answer for the numerator of step 6,
I'm not sure how the square roots cancel out and what square root of x+h or x is but lets say I do know why they cancel out and then I show the next step, so I'm following BEDMAS and I'm left with ((x+h)^2 - (x)^2) = ((x+h)(x+h) - (x)(x)) = x^2+xh+xh+h^2 - x^2 = 2xh + h^2,
so I've already messed up there but I guess I'm just really confused with this problem and any help to explain it is appreciated! Thanks for your time and help.
step 1 = sqrt(x+h)-sqrt(x)
h
2 = sqrt(x+h)-sqrt(x) * sqrt(x+h)+sqrt(x)
h * sqrt(x+h)+sqrt(x)
3 = (sqrt(x+h)-sqrt(x)(sqrt(x+h)+sqrt(x))
h(sqrt(x+h)+sqrt(x))
4 = ((sqrt(x+h))^2-(sqrt(x))^2)
h(sqrt(x+h)+sqrt(x))
5 = (x+h-x)
h(sqrt(x+h)+sqrt(x))
6 = h
h(sqrt(x+h)+sqrt(x))
7 = 1
sqrt(x+h)+sqrt(x)
8 = lim h ->0 1
sqrt(x+h)+sqrt(x)
9 = 1
2sqrt(x)
and I'm wondering how they decide to take the whole numerator in step 1 and multiply it to the denominator and then also in step 2 why do they switch the -sqrt(x) to +sqrt(x)? Also in step 4 to 5 to 6 it arrives at h but how, they don't really show the steps they took, if I were to do it I guess would come up with this answer for the numerator of step 6,
I'm not sure how the square roots cancel out and what square root of x+h or x is but lets say I do know why they cancel out and then I show the next step, so I'm following BEDMAS and I'm left with ((x+h)^2 - (x)^2) = ((x+h)(x+h) - (x)(x)) = x^2+xh+xh+h^2 - x^2 = 2xh + h^2,
so I've already messed up there but I guess I'm just really confused with this problem and any help to explain it is appreciated! Thanks for your time and help.
Last edited: